Interprovincial Wealth Inequality by Factor Components in Indonesia - Soseco, T.; Olivia, S.; Oxley, Leslie (2024)
This paper investigates three issues related to interprovincial inequality in household net wealth in Indonesia. First, it assesses whether inequality is dominated by inequality within or between provinces. Second, it identifies the determinants of inequality. Third, it looks at the clubs of regions formed owing to convergence or divergence in household net wealth growth in Indonesia. Using data from five waves of the Indonesian Family Life Survey, we found declining inequality in household net wealth in Indonesia, dominated by inequality within provinces. Education is the biggest equalising variable for inequality in household net wealth in Indonesia. Using a club convergence approach, we also found that growth in household net wealth converged within one club and that two clubs converged over time.